Pedunculated oral fibroma in an 11-year-old patient: A case study - Issa Saad; Maya Jokhadar; Mohamad Salem Rkab; Ahmad Al Manadili; Marwan Al-Raeei; Chadi Azmeh; Mohamad Kamel Alhariri; Mohamad Hasem; Rgena Khalil; Yussef Kalo; Ammar Nasser Agha; Waad Omran (Oral Oncology Reports)
Fibroma, known as irritable fibroma, is the most prevalent oral fibrous tumorlike growth. Despite being referred to as a benign tumor, most fibroids are actually focal reactive fibrous enlargements caused by trauma or local irritation. Although the term focal fibrous hyperplasia provides a more accurate description of the clinical appearance and development of this condition, it is not commonly utilized. Clinically, fibroma manifests as a well-defined, slow-growing, pedunculated or sessile mass with a smooth surface, normal color, and no pain. It typically affects individuals between the ages of 30 and 50. This case report presents the case of an 11-year-old Syrian patient with an oral fibroma located on the right side of the buccal mucosa. The patient, an 11-year-old Syrian boy, visited the oral and maxillofacial surgery clinic with a ball-shaped mass in the mouth. Intraoral examination revealed a firm, oval-shaped nodule covered by healthy mucosa. Radiographic examination showed no presence of calcifications. The mass was surgically removed under local anesthesia and subsequently sent for histopathological assessment. Histopathology findings revealed a well-defined mass consisting of dense collagenous stroma and fibroblasts, leading to the diagnosis of traumatic fibroma. The treatment involved complete surgical excision. Traumatic fibromas can affect individuals of any age and gender, potentially leading to obstruction or enlargement.